Alloy gray cast iron material for locomotive brake disc, and casting method of alloy gray cast iron material - ZHU HAIYANG; YIN SHEXIN (2015)
The invention relates to an alloy gray cast iron material for a locomotive brake disc, and a casting method of the alloy gray cast iron material. Eight raw materials including steel scrap, cast iron ingots, silicon iron, manganese iron, ferrochromium, electrolytic tin, electrolytic nickel and electrolytic copper are adopted; the method comprises the following steps: carrying out shot blast cleaning on the cast iron ingots and the steel scrap, putting the raw materials into a furnace, melting, sampling at the stokehole, testing the chemical composition of the alloy gray cast iron material, molding by casting, and the like; the mechanical performances of the obtained alloy gray cast iron material for the locomotive brake disc reach the following standards: the tensile strength (Be b MPa) is more than or equal to 295, and the Brinell hardness (HBW) is more than or equal to 200-240. The alloy gray cast iron material is a low-alloying wear-resistant material, and has a stable metallographic structure and mechanical property; the alloy gray cast iron material is used for producing the brake disc, and the physical and chemical performance standards of the brake disc are superior to those of the similar abroad products. The metallographic structure and comprehensive mechanical performance of the alloy gray cast iron material are much better than those of the similar abroad products; the service life of the alloy gray cast iron material exceeds 2 million kilometers.